Effect of socio-demographic factors, family information and gynecology history on ultrasound breast morphologyin different age groups - Abdulwahhab Ibraheem, Shahad; Mahmud, Rozi; Mohamad Saini, Suraini; Bahari, Norafida; Alazzwi, Mousa (Global Journals, 2017)
Background: A number of factors such as age, hormones, reproductive history, diet and genetics influence the morphology of a woman’s breast. A study conducted found age, hormones, reproductive history, genetics and diet (body habitus) to be the major contributors to breast density. The purpose of this study was to assess knowledge and find association of breast morphology with socio-demographic factors, family information and gynecology history by ultrasound. Methods: A self-administration questionnaire that included information of patients and an analytic cross-sectional study design was used to determine the morphology of normal breast among all respondent that attending the imaging department of Golden Horses Health Sanctuary, Sri-Kembangan located in Klang Valley, Selangor, Malaysia. All women were subjected to bilateral whole breast ultrasound using ultrasound.